AFL Teachers’ Reflective Practice in Indonesia: Connection Between Learning and Teaching: الممارسة الإنعكاسية لمعلمي اللغة العربية كلغة أجنبية في إندونيسيا: الروابط بين التعلم والتعليم - Fauzi, Ihsan; Nurbayan, Yayan; Nursyamsiah, Nunung (Institut Agama Islam Negeri Palangka Raya, 2023)
In Indonesia, currently Arabic teaching is predominantly teacher-centered and textbook-based. This study helps clarify how each reflective practice of Arabic as a foreign language (AFL) teachers can form and build their professional identity in teaching using sociocultural theory and reflective practice. The information gathered through narrative interviews shows that today